Efficiency in Human Resource Management through the Digital System “Satu Kemenkeu”: An Evaluation of Automation within the Ministry of Finance in Indonesia - Erwin, E.; Riau, Dwi Putranto; Akadira, Tora (Golden Ratio of Human Resource Management, 2025)
This study aims to evaluate the effectiveness of the digital automation system "Satu Kemenkeu" in enhancing human resource management (HRM) efficiency and productivity within the Ministry of Finance. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving 18 informants from various hierarchical levels. The findings indicate that the implementation of the system has reduced administrative service time by up to 43.7%, increased daily data entry volume from 24 to 47 entries per officer, and accelerated performance reporting by 53%. Moreover, the application provides real-time data access and incorporates performance evaluation features based on objective indicators, strengthening managerial decision-making processes. Nonetheless, challenges such as digital literacy gaps, reliance on central technical units, and limited regional infrastructure continue to hinder the system's optimal performance. The study recommends comprehensive user training strategies, reinforcement of local technical support, and the development of data-driven feedback mechanisms to ensure the sustainability of digital transformation in public sector HRM.